Epithelial immunotherapy for food allergy in children: a systematic review and meta-analysis - Chen, Bin; Gao, Hu; Li, Xihong; Zou, Zhuan; Wu, Shanshan; Tang, Fajuan (Frontiers in Immunology, 2024)
ObjectivesTraditional methods of treating allergies primarily revolve around avoiding allergens and promptly using rescue medications when allergic symptoms occur. However, this approach is known for its inefficiency and limited success in achieving long-term relief. Our aim was to conduct a comprehensive analysis of previously published randomized controlled trials (RCTs) that explore the effectiveness and safety of epicutaneous immunotherapy (EPIT) as a means to manage food allergies in children.MethodsWe conducted a comprehensive search across multiple databases, including PubMed, Web of Science, Embase, and Cochrane Library, to identify RCTs comparing EPIT versus placebo for the management of allergen-triggered allergic reactions in children. Only RCTs published in English that evaluated the efficacy and safety of EPIT in pediatric patients with allergic diseases were considered eligible for inclusion. The quality assessment of the included studies was performed using the Cochrane risk-of-bias tool. The analysis comprised of seven RCTs involving a total of 1141 participants. The meta-analysis demonstrated that EPIT significantly facilitated desensitization in patients with food allergy (RR: 2.12, 95% CI: 1.74-2.59, P = 0.296, I² = 17.5%), particularly in individuals with peanut allergy (RR: 2.29, 95% CI: 1.83-2.86, P = 0.463, I² = 0%). However, it is important to note that EPIT was associated with an increased occurrence of treatment-related adverse events (TRAEs; RR: 1.24, 95% CI: 1.14-1.34, P < 0.01, I² = 99.2%). Notably, there were no notable disparities in the frequency of serious adverse events or utilization of rescue medications between the EPIT and placebo groups. EPIT may potentially induce desensitization of peanut allergy in children, but also carries an elevated risk of TRAEs.